2013
DOI: 10.1158/0008-5472.can-12-3150
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Function of the Plasma Glutathione Peroxidase Gpx3 in Colitis-Associated Carcinoma

Abstract: The glutathione peroxidases, a family of selenocysteine-containing redox enzymes, play pivotal roles in balancing the signaling, immunomodulatory and deleterious effects of reactive oxygen species (ROS). The glutathione peroxidase GPX3 is the only extracellular member of this family, suggesting it may defend cells against ROS in the extracellular environment. Notably, GPX3 hypermethylation and underexpression occurs commonly in prostate, gastric, cervical, thyroid and colon cancers. We took a reverse genetics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 46 publications
4
143
1
Order By: Relevance
“…Of note, the matched tumor/normal pairs from the same patients allow an unbiased and efficient analysis of the H3K4me3 width. As observed in cell lines, broad H3K4me3 in normal lung tissues is associated with tumor suppressors (Fig 7a) and shortening of broad H3K4me3 is frequently observed at established tumor suppressors, such as GPX3 35 and PLK2 3638 (Fig 7b). In total, we identified 209, 108, and 248 genes with shortened, lengthened, and stable broad H3K4me3 in lung tumors relative to normal lung tissues (Fig 7c).…”
Section: Resultssupporting
confidence: 54%
“…Of note, the matched tumor/normal pairs from the same patients allow an unbiased and efficient analysis of the H3K4me3 width. As observed in cell lines, broad H3K4me3 in normal lung tissues is associated with tumor suppressors (Fig 7a) and shortening of broad H3K4me3 is frequently observed at established tumor suppressors, such as GPX3 35 and PLK2 3638 (Fig 7b). In total, we identified 209, 108, and 248 genes with shortened, lengthened, and stable broad H3K4me3 in lung tumors relative to normal lung tissues (Fig 7c).…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, a recent study has shown GPX3 hypermethylation and underexpression in human colon cancer. This study demonstrated that GPX3-deficient mouse model exhibited increased inflammation and tumor number, suggesting that loss of GPX3 is involved in inflammatory colonic tumorigenesis 45. Of major importance, the fact that neutral bile salts are still capable of activating NF-κB pathway and up-regulating pro-inflammatory cytokines and chemokines in esophageal epithelium, strongly suggests that strategies focusing on reducing acids only in GERD patients may not be sufficient to prevent the development of BE and/or progression to EAC.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, the list was enriched for genes related to oxidoreductase activity (five genes: AOX1, PTGS1, ACOX2, COX7A1, and the tumor suppressor GPX3; ref. 22). Because the downregulation is seen in both cancer cell lines and primary tumors, we deduce that the changes are caused by a permanent reprograming of metabolism in cancer cells rather than response to tumor microenvironment, or cell culture conditions.…”
Section: Potential Pan-cancer Biomarkersmentioning
confidence: 81%